PENGARUH MEDIA AUDIO VISUAL TERHADAP MINAT BELAJAR SISWA KELAS X PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK IBNU SINA GENTENG - Mashuri, Imam; Rofiq, Ainur; Ismawati, Mamik (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This research aims to find out the influence of media use and the extent of things that affect students' learning interests by using the teacher's audio visual media in conveying concepts, ideas, sciences and experiences to students who can be captured using the senses of sight and hearing so that the goals that have been set aside to learners can be achieved. This research is a quantative study with a type of field research. The subject of this study was grade X students of SMK Ibnu Sina Genteng with a sample of 30 students from 100 population using random sampling techniques. Data collection techniques using observations, polls, interviews and documentation. Test validity using product moment formula and test its reality using cronbach alpha formula. While the hypothesis test in this study uses linear regression techniques. The results of the study prove that (1) the influence of Audio Visual Media on students' learning interests in SMK Ibnu Sina Genteng is caused by indicators of student learning interests ranging from feelings of pleasure, student interest, student attention, and student involvement caused by a value of F count = 5,122 with a signification rate of 0.000 > 0.005, then there is the Influence of Audio Visual Media on the Interest of Learning Students alternative hypotheses accepted and zero hypothesis rejected. (2) The extent of Audio Visual Media's influence on learning interests starts from the factor of motivation in, social motivational factors and emotional factors. Obtained through a hypothesis test using a simple linear regression test formula, it was found that there was a positive influence of each variable with the result of variable X regression coefficient of 0.025 of variable Y of 71,718, meaning there was an Influence of Audio Visual Media on students' Learning Interests.